(untitled) (Journal of Imam Al-Kadhim College, 2023)
The Crim of military buildup against a foreign country is considered on of the crimes against the foreign state that the Iraqi legislator dealt with under Article ( 165) of part on of B ook Two of the amended penal code nomper 111 of 1969, and it is one the early crimes that are accomplished once its criminal behavior of mobilization is achieved military against a foreign country.